Floods as agents of vitality: reaffirming human-nature synergies - Modak, S.; Ghosh, Surajit (Water Science Policy gUG, 2021)
The policy response for flood governance should be based on the premise that floods in monsoon-dominated landscapes such as the Ganga-Brahmaputra-Meghna (GBM) basin are inevitable.